2020
DOI: 10.1007/s13755-020-00116-6
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of multiresolution approaches for chest X-ray image based COVID-19 detection

Abstract: COVID-19 is a novel virus, which has a fast spreading rate, and now it is seen all around the world. The case and death numbers are increasing day by day. Some tests have been used to determine the COVID-19. Chest X-ray and chest computerized tomography (CT) are two important imaging tools for determination and monitoring of COVID-19. And new methods have been searching for determination of the COVID-19. In this paper, the investigation of various multiresolution approaches in detection of COVID-19 is carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 25 publications
0
38
1
Order By: Relevance
“…Ismael et al. [23] also used multiresolution approaches namely, Shearlets, Wavelets, and Contourlet transforms for COVID-19 detection. The researchers represented more improved results than the deep learning method’s achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Ismael et al. [23] also used multiresolution approaches namely, Shearlets, Wavelets, and Contourlet transforms for COVID-19 detection. The researchers represented more improved results than the deep learning method’s achievements.…”
Section: Introductionmentioning
confidence: 99%
“…Adding processes that improve feature selection also improved performance, including correlation‐based feature selection, 60 feature categorisation with decision trees, 61,62 SVMs 63 and even handpicking features 64 …”
Section: Automatic Disease Detection On Cxr Imagesmentioning
confidence: 99%
“…Some papers demonstrated that DNN outperformed traditional models 79 and reduced computational cost of detection with high performance while maintaining good performance, especially those with minimal convolutional and fully connected layers. Ismael 63 demonstrated that non‐DL methods can still be effective at detecting COVID‐19 pneumonia using multiresolution approaches.…”
Section: Automatic Disease Detection On Cxr Imagesmentioning
confidence: 99%
“…In order to automate COVID-19 detection/recognition from CXR images, several studies [21][22][23] have extracted features from the CXRs to utilize Support Vector Machines classifier. On the other hand, many studies [17,[24][25][26][27][28][29][30][31][32] have proposed to use deep Convolutional Neural Networks (CNNs).…”
Section: Introductionmentioning
confidence: 99%